PENGARUH CITRA MEREK, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN NANNYS’S PAVILLON - Barwana, Lisbet; Fairliantina,, Edvin (Jurnal Nusantara Mandani, 2023)
This study aims to determine the effect of brand image, promotion and product quality on purchasing decisions at Nanny's Pavillon Sumarecon Mall Bekasi. Background: The problem raised in this study is whether there is a positive and significant relationship between brand image, promotion, and product quality on purchasing decisions. Subjects and Methods: the sampling method used is purposive sampling with 93 respondents, where a sample of 20 people has been tested for validity and reliability. As for the correspondent data as many as 73 people. The research method used in this study uses the classical assumption test, multiple regression analysis, F test and T. Test: The results of the regression calculation obtained from the value Purchase decision (Y) = 1.073 + 0.456 (brand image X1) + 0.125 (promotion X2) + 0.419 (product quality X3). The results of the T-test calculation of the calculated sig value <0.05 where the results of brand image and product quality are 0.000 which means less than 0.05, while the T-test result of promotion is 0.192 which means it is not significant because the promotion value is greater than 0.05. Conclusion: that the brand image, and product quality of Nanny's Pavillon all have an impact on buyer choice. Brand image and product quality strongly influence purchasing decisions at Nanny's Pavillon, but promotion has no significant effect on purchasing decisions at Nanny's Pavillon Sumarecon Mall Bekasi.